Alisher Navoi's Influence on World Literature through Translation (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2024)
This article explores the influence of Alisher Navoi, a prominent figure in Uzbek literature, on world literature through his translation efforts and their impact on cultural exchange. By analyzing his works and their dissemination, the study examines how Navoi's literary and linguistic innovations enriched global literary traditions. Methods include textual analysis and comparative literary studies. The findings suggest that Navoi’s translations bridged linguistic and cultural divides, fostering mutual understanding among diverse civilizations. The article concludes by emphasizing Navoi’s enduring legacy in promoting intercultural dialogue.